St. James Avenue, Trinidad - (:unkn) unknown (My University, 2010)
A view of tree lined St. James Avenue.
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Suburbs; Cities and towns--St. James